Phytosomes: nature’s secret to enhanced bioavailability - Kumar, M Surendra; Dhivya, K; Lokesh, D; Nivethitha, S; Kumar, M Praveen; Sarathi, M; Astalakshmi, N (Creative Pharma Assent, 2024)
Background: Medicinal herbs have long been used for treating various ailments, with plant-derived compounds recognized for their therapeutic benefits and minimal side effects compared to conventional medicines. However, issues with the bioavailability of active herbal components have limited their effectiveness. Phytosomes, or herbosomes, are a drug delivery technology that enhances the absorption and bioavailability of these plant-based compounds, providing a potential solution for maximizing the medicinal efficacy of herbal ingredients. Method: Phytosome complexes are synthesized by combining plant extracts with phospholipids in specific molar ratios, typically 1:1, to create a more stable and bioavailable formulation. Common preparation methods include solvent evaporation, supercritical fluid extraction, and lyophilization. Each technique is optimized to improve the stability, solubility, and therapeutic action of the phytosomes. Results and discussion: Phytosome technology has shown significant improvements in the bioavailability of phytochemicals, such as silymarin and curcumin, enhancing their pharmacological effects. Applications of phytosomes span various therapeutic areas, including cancer treatment, rheumatism, wound healing, and respiratory conditions. Studies indicate that phytosomes improve drug stability, absorption, and targeted delivery, effectively managing complex diseases with reduced side effects. Conclusion: Phytosomes represent a promising advancement in natural medicine by addressing bioavailability challenges associated with herbal compounds. The improved formulation techniques and broad applications suggest a bright future for phytosome-based therapies, especially in areas where conventional treatments may have limitations. Further research and development in phytosome technology could lead to enhanced clinical outcomes and expand the use of herbal remedies in modern medicine.